Relevance of Staff Development Courses in Addressing Pedagogical Needs of University Academic Staff in Tanzania - Matiba, Fortunatha (Papers in Education and Development, 2020)
This study investigated the relevance of staff development courses offered in two Tanzanian universities to establish whether or not they respond to the lecturers ' pedagogical needs. Three objectives guided this study, which were to: (a) Examine the staff development courses offered in the two universities; (b) explore academic members of staff ' s pedagogical needs; and (c) examine the views of academic members of staff on the relevance of development courses offered in meeting their pedagogical needs. The study employed a qualitative research approach, with multiple case study designs. A total of 38 participants were studied. Semi-structured interviews and documentary review were the main data collection tools. The study findings indicate that the two universities offered several staff development courses mainly in teaching and research. Teaching courses included teaching how to teach large classes and integrating technology in teaching. Moreover, the study found that academic members of staff had varied staff development needs based on the respective university ' s core functions, especially research and teaching. However majority of academics viewed the courses offered as not relevant enough to meet their pedagogical needs. Based on the study findings, it is apparent that, unless universities offer courses that cater for academic staff ' s actual needs, the efforts and resources invested in providing staff development courses would be more of a waste than an investment. The study therefore, recommends for universities to offer up-to-date and relevant knowledge that caters for academic staff needs to realise their core functions. Keywords: Higher education, pedagogical needs, staff professional development programmes